2003
DOI: 10.1093/nar/gkg573
|View full text |Cite
|
Sign up to set email alerts
|

WU-Blast2 server at the European Bioinformatics Institute

Abstract: Since 1995, the WU-BLAST programs (http://blast.wustl.edu) have provided a fast, flexible and reliable method for similarity searching of biological sequence databases. The software is in use at many locales and web sites. The European Bioinformatics Institute's WU-Blast2 (http://www.ebi.ac.uk/blast2/) server has been providing free access to these search services since 1997 and today supports many features that both enhance the usability and expand on the scope of the software.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
96
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 24 publications
0
96
0
Order By: Relevance
“…The annotation procedure consists of two major steps. First, C. remanei genomic sequences that encode candidate ABC genes by using C. elegans ABC genes as query to search the C. remanei genomic sequences database using WU-BLAST (tblastn) (Lopez et al 2003). Regions that best match the query C. elegans ABC genes were parsed and recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The annotation procedure consists of two major steps. First, C. remanei genomic sequences that encode candidate ABC genes by using C. elegans ABC genes as query to search the C. remanei genomic sequences database using WU-BLAST (tblastn) (Lopez et al 2003). Regions that best match the query C. elegans ABC genes were parsed and recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Structural and Functional Homologs-In a search for related homologs of B. subtilis imidazolonepropionase using BLAST (32), it is observed that the enzyme exists widely in various organisms. We picked HutI proteins from representative Gram-negative, Gram-positive bacteria, and eukaryotes, respectively and aligned these sequences with ClustalX and ESPript (Fig.…”
Section: ⑀2mentioning
confidence: 99%
“…We compared the performance of genBlastA with two existing programs with similar functionalities-WU-BLAST (Lopez et al 2003) and the program by Cui et al (2007). WU-BLAST is available by an academic license.…”
Section: Test Gene Set Preparation and Test Strategymentioning
confidence: 99%
“…With recent advances in sequencing technologies (Margulies et al 2005;Bentley 2006), the volume of the nucleotide sequences is expanding at an accelerating pace, further enriching genomic sequence resources. To effectively exploit these resources for biological and medical research, many homology-based similarity search and alignment tools have been developed over the past 20 yr. Representative similarity search and alignment tools include BLAST (Altschul et al 1990), FASTA (Pearson and Lipman 1988), sim4 (Florea et al 1998), WU-BLAST (Lopez et al 2003), and BLAT (Kent 2002). These tools have been extremely useful, especially for comparative genomics, in which genomes of both closely and distantly related species are compared in order that knowledge of the genome of one species can be used to understand the genome of other species (Hardison 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation